Risk Factors for Recent Suicide Attempts in Major Depressive Disorder Patients in China: Results From a National Study - Xin, Li-Min; Chen, Lin; Su, Yun-Ai; Yang, Fu-De; Wang, Gang; Fang, Yi-Ru; Lu, Zheng; Yang, Hai-Chen; Hu, Jian; Chen, Zhi-Yu; Huang, Yi; Sun, Jing; et al. (Frontiers in Psychiatry, 2018)
Objective: To analyze the factors associated with recent suicide attempts including socio-demographic and clinical characteristics in major depressive disorder (MDD) patients in China. Methods: The data were from a nationwide sample from 13 major psychiatric hospitals or the psychiatric units of general hospitals in China, from September 1, 2010 to February 28, 2011. Melancholic features and suicide attempts in the past month were defined according to the melancholic feature module and the suicide module of the Mini International Neuropsychiatric Interview (MINI). Socio-demographic and clinical characteristics were compared between MDD patients with and without recent suicide attempts. Further analyses regarding the factors associated with recent suicide attempts in MDD patients were performed via multivariate logistic regression analysis. Results: Among 1,172 MDD patients, 57 (4.9%) were reported to have made a suicide attempt in the past month. Compared to the MDD patients without recent suicide attempt, significantly higher percentage of patients in the recent suicide attempters group had previous suicide attempts (χ2 = 171.861, p < 0.001) and depressive episodes with melancholic features (χ2 = 22.837, p < 0.001). Logistic regression analysis indicated that previous suicide attempts (OR = 20.81, 95% CI: 11.12–38.94, p < 0.001) and depressive episodes with melancholic features (OR = 4.43, 95% CI: 2.09–9.43, p < 0.001) were independently associated with recent suicide attempts in MDD patients. Limitations: Cross-sectional design, retrospective recall of suicide attempt data. Conclusion: Recent suicide attempts are associated with melancholic features and previous suicide attempts in MDD patients in China. These data may help clinicians to identify MDD patients at high risk of suicide attempt behavior.